Kesantunan Berbahasa di Era Digital: Tinjauan Analisis Moral Pada Komentar Berita Sepakbola di Akun Instagram Pengamat sepak bola - Purwati Purwati; Indra Gunawan (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2019)
Social media is a new space for the public to interact in the digital era. This crowded means of interaction raises new problems in social relations that is the number of netizens who use abusive language in comments. As a result, social media becomes a tool to insult people, fight and spread hatred. Therefore, this study has the aim to describe the use of impolite language of netizens in the social media comment column and the factors that influence it. This study uses a qualitative descriptive approach, note taking techniques, theory triangulation, and analysis techniques based on a moral’s point of view. The subject is netizens, while the object is politeness in language on social media. The results of this study are: a) netizens' language in commenting is categorized as impolite because it is contrary to the maxim of wisdom, generosity, appreciation, simplicity, consensus, and sympathy; b) factors that influence netizens in commenting are moral knowledge, recognized needs, mental readiness to accept new public spaces, cyberspace character, equality and a sense of friendship. Based on this research, it is needed material for digital society in using social media.